Medical assistance in fighting against COVID-19 in Wuhan, China: A frontline nurse's experience and lessons learned - Qian-Qian Li; Feng-Li Gao (Wolters Kluwer Medknow Publications, 2020)
This article shared personal experiences of encountering challenges during the work at the frontline fighting against COVID-19 in Wuhan, China, and found solutions and suggestions to overcome the challenges during the period, including solutions to address challenges encountered during work, suggestions for smooth communication among different parties, and suggestions for optimizing work regulations and workflow and establishing behavior habits and professional knowledge and practices. These experiences would be helpful for health-care workers to fight against the pandemic.